A facile turn‐on chemiluminescence probe for sensitive imaging on aminopeptidase N activity. (28th June 2022) - Sun, Ru; Wu, Xuesong; Mao, Yanjia; Wang, Hongbo; Bian, Chong; Lv, Panpan; Zhao, Zhen; Li, Xinwei; Fu, Wei; Lu, Jianzhong; Cao, Zhijuan
Abstract: Aminopeptidase N, as a target for drug discovery, shows marked relationships with many diseases, especially liver injury and cancer. Here, we explored a chemiluminescence (CL) probe for sensing APN by tethering the APN‐specific substrate group to the ortho‐acrylated phenoxy‐dioxetane scaffold. In this way, two CL probes (APN‐CL and BAPN‐CL ) were designed with noncapped leucine and butoxy‐carbonyl capped leucine as the protecting group to preserve the chemiexcitation energy. The uncovered leucine was demonstrated to be essential for detection of APN activity by comparing the CL intensity of two CL probes. Probe APN ‐CL was turned on upon APN cleavage, resulting in a high chemiluminescent emission, whereas the chemiexcitation energy of probe BAPN‐CL was still restrained even with the high‐level APN. The result was further elucidated by molecular docking simulations. Probe APN ‐CL exhibited a fast response and high sensitivity with a detection limit of 0.068 U/L, and an excellent specificity for the discrimination of APN from biological ions, small molecules, and other proteases commonly found in living system. By virtue of good stability and cell viability, probe APN ‐CL imaged abnormal levels of APN in tumour cells and tumour‐bearing mice. Moreover, this probe APN‐CL could be easily used to evaluate APN inhibitors and APN levels in plasma samples from 20 patients. Overall, as a facile and cost‐effective probe, APN ‐CL will be a promising alternative in the early diagnosis of pathologies and for cost‐effective screening of inhibitors. Abstract : We developed a chemiluminescence probe (APN‐CL) for protease APN detection by tethering APN‐specific substrate to the phenoxy‐dioxetane scaffold. Probe APN‐CL was turned on to exhibit a high chemiluminescent emission upon APN cleavage with excellent specificity and sensitivity in vitro and in living system, thus offering a facile and cost‐effective alternative in the early detection of pathologies and inhibitors screening.